2013
DOI: 10.1007/jhep04(2013)092
|View full text |Cite
|
Sign up to set email alerts
|

The Navier–Stokes equation and solution generating symmetries from holography

Abstract: The fluid-gravity correspondence provides us with explicit spacetime metrics that are holographically dual to (non-)relativistic nonlinear hydrodynamics. The vacuum Einstein equations, in the presence of a Killing vector, possess solution-generating symmetries known as spacetime Ehlers transformations. These form a subgroup of the larger generalized Ehlers group acting on spacetimes with arbitrary matter content. We apply this generalized Ehlers group, in the presence of Killing isometries, to vacuum metrics w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Following the ideas of [40], we employ a similar reasoning to the flat metric discussed in chapter 3, which is done by solving the Killing equations perturbatively in the ε-expansion. We also found that Ehlers transformations may relate the Rindler and Taub spacetimes.…”
Section: Outline Of This Dissertationmentioning
confidence: 99%
See 4 more Smart Citations
“…Following the ideas of [40], we employ a similar reasoning to the flat metric discussed in chapter 3, which is done by solving the Killing equations perturbatively in the ε-expansion. We also found that Ehlers transformations may relate the Rindler and Taub spacetimes.…”
Section: Outline Of This Dissertationmentioning
confidence: 99%
“…For convenience, we are going to adopt the nomenclature used in [39,40]: we shall refer to the general transformations described by eq. (4.1) as the generalized Ehlers group, while their subset which specifically maps vacuum solutions into vacuum solutions shall be called the spacetime Ehlers group.…”
Section: Chapter 4 Solution-generating Symmetriesmentioning
confidence: 99%
See 3 more Smart Citations